USM, XINYANG UNIVERSITY TO PURSUE ACADEMIC AND RESEARCH COLLABORATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 12 December 2016 Universiti Sains Malaysia (USM) today received an official courtesy visit from the delegates of Xinyang University, China to discuss and identify potential areas of mutual interest for academic and research collaborations.